Association of traditional Chinese medicine therapy and the risk of dementia in patients with hypertension: a nationwide population-based cohort study - Kuen-Hau Chen; Ming-Hsien Yeh; Hanoch Livneh; Bor-Chyuan Chen; I-Hsin Lin; Ming-Chi Lu; Tzung-Yi Tsai; Chia-Chou Yeh (BMC Complementary and Alternative Medicine, 2017)
Abstract Background Patients with hypertension (HTN) reportedly have a higher risk of developing dementia. However, it remains unclear if use of Traditional Chinese Medicine (TCM), the most common form of complementary and alternative medicine, can help lower the risk of dementia for these patients. So the aim of the study was to investigate the effects of TCM on dementia risk among patients with hypertension. Methods This longitudinal cohort study used the Taiwanese National Health Insurance Research Database (NHIRD) to identify 143,382 newly diagnosed hypertension patients aged 20–90 years who received treatment between 1998 and 2007. Among them, 52,365 (36.52%) had received TCM after the onset of hypertension (TCM users), and the remaining 91,017 patients (63.48%) were designated as a control group (non-TCM users). All enrollees were followed until the end of 2012 to record the incidence of dementia. A Cox proportional hazards regression model was used to compute the hazard ratio (HR) of dementia in patients who received TCM. Results During the 15-year follow-up, 3933 TCM users and 10,316 non-TCM users developed dementia, representing an incidence rate of 8.41 and 11.55%, respectively, per 1000 person-years. TCM users had a significantly reduced risk of dementia compared to non-TCM users (adjusted HR = 0.76; 95% confidence interval [CI] = 0.74–0.81). The predominant effect was observed among those treated with TCM longer than 180 days (adjusted HR = 0.65; 95% CI = 0.62–0.69). Among the commonly used TCM products, Tian-Ma-Gou-Teng-Yin, Dan-Shen (Radix Salviae Miltiorrhizae), Chuan-Niu-Xi (Radix Cyathulae), Ge-Gen (Radix Puerariae), Jia-Wei-Xiao-Yao-San, and Jue-Ming-Zi (Semen Cassiae) were significantly associated with a lower risk of dementia. Conclusions Results from this population-based study support the effects of TCM on reducing dementia risk, which may provide a reference for dementia prevention strategies.